Knowledge and attitude towards dental clinical practice related to COVID-19 pandemic among dental interns in Saudi Arabia - Suhail Shariff; Muath Muhammad Benten; Mohammed Khaled Ahmed Al-Zabidi; Ghaida Mohammed Alshehri; Ahad Abdulaziz Almehmadi; Shahad T F Alhazmi; Elaf Waleed AlDara (Wolters Kluwer Medknow Publications, 2021)
Background: The newly emerged pandemic has created many dilemmas in dental clinical practice all over the world. Most of the practicing dentists and dental students are at higher risk of getting infected and transmitted the disease. The study aimed to explore the knowledge and attitudes among dental interns in Saudi Arabia related to the COVID-19 pandemic. Materials and Methods: An online questionnaire survey was carried out among dental students pursuing their internship at different universities in Saudi Arabia. A combination of convenience and snowball sampling was used to identify interns from each province of the Kingdom. The questionnaire was validated and pretested, which recorded the knowledge, attitude, and concerns related to dental practice and COVID-19. Results: The knowledge related to COVID-19 and its importance in clinical dental practice was below average among dental interns, and only 22.2% gave a correct response to all questions. About 80.8% and 85% of the dental students were worried about contracting the infection during dental practice and transmitting it to family and friends, respectively. Conclusion: Dental students showed satisfactory knowledge, attitude, and practices related to COVID-19, and most of them were aware and adhering to the preventive guidelines set by the ministry of health.